The Effectiveness of Flavonoids in Pigeon Pea (Cajanus cajan) as Inhibitors of α-Glucosidase Enzyme in Anti-diabetes - Ginaris, Rifkarosita Putri; Fauzah, Na’imatul Retno (FITOFARMAKA: JURNAL ILMIAH FARMASI, 2023)
Diabetes mellitus is a metabolic disease characterized by hyperglycemia, due to relative and absolute insulin deficiency of the body. Acarbose is a drug that can be used to treat diabetes mellitus, especially type II diabetes mellitus. Type II diabetes mellitus is an endocrine disease that causes 95 % of deaths worldwide. Gude bean extract (Cajanus cajan) is one alternative to the use of natural anti-diabetic medicine, containing saponins, flavonoids, phenolics, and tannins. Flavonoids are antioxidant compounds that have a hypoglycemia effect in people with diabetes mellitus. This study aimed to test the inhibitory activity of alpha-glucosidase enzyme from gude bean extract. The enzyme α-glucosidase activity was quantified by measuring the quantity of para-nitrophenol generated at a wavelength of 405 nm. The inhibitory power of the α-glucosidase enzyme was seen from the IC50 value. Gude Bean Extract has the ability to inhibit the enzyme α-glucosidase resulting in an IC50 value of 69.67 ppm strong level activity. Gude Bean Extract has the ability to inhibit the enzyme α-glucosidase resulting in an IC50 value of 69.67 ppm with a strong strength level